Co-expressing LRP6 With Anti-CD19 CAR-T Cells for Improved Therapeutic Effect Against B-ALL - He, Ping; Tan, Zhongqiu; Wei, Zhongheng; Wan, Cheng-Liang; Yang, Shan-Shan (Frontiers in Oncology, 2020)
Background Cellular immunotherapy such as chimeric antigen receptor modified-T cell (CAR-T) therapy presents with an excellent potential for tumor treatment. The memory phenotype of CAR-T has been correlated positively with therapeutic effect and prognosis of cancer. Method The proliferation rates of a novel CAR-T was determined by cell counting. The phenotypes of CAR-T cells were then detected by flow cytometry. The cell cytotoxicity against tumor cells in vitro was investigated by lactate dehydrogenase (LDH) assay and luciferase assay. The cytokines secreted during these assays were determined by the cytometric bead array (CBA) assay. The antitumor ability in vivo was evaluated in NOG mice. Results Co-expression of LRP6 full-length protein with anti-CD19 CAR significantly improved the memory phenotype of CAR-positive T-cells by enhancing the wnt signaling pathway. As compared with anti-CD19 CAR-T, anti-CD19 CAR-T-LRP6 exhibited more robust cytotoxicity against tumor cells in vitro and in vivo, albeit fewer cytokines were released in vitro. Moreover, the longer survival and robust expansion in vivo of anti-CD19 CAR-T-LRP6 cells were found to be effective in inhibiting cancer recurrence. Conclusions CAR co-expressed with LRP6 could sustain the memory phenotype that enabled permanent relief and may further assist in the development of potent and durable T-cell therapeutics.